Art is health - Pollmann, Claudia (Socialmedicinsk tidskrift, 2019)
For Health is art, Prof. Tyyne Claudia Pollmann will flip the terms and introduce a reverse perspective on the topic, Art is health. She will follow the thread Make sense - Enrich environments – Make more sense - Collaborate.